REDESIGN CUTTING MACHINEMELALUI METODE PENDEKATAN DESIGN FOR MANUFACTURING AND ASSEMBLY (DFMA) - Pramudya Budi Kurniawan; Subekti Subekti (Program Studi Teknik Mesin Universitas Tarumanagara, 2021)
The muffler has a function to reduce loud and noisy sounds that come out of the exhaust gas manifold of motorized vehicles. One of the main components of the muffler part is the body inner. In producing the body inner, special machine tools are needed to assist the production process, such as cutting machines. The assembly and manufacturing processes have an important role in the development of the cutting machine products made in this research. This study aims to design a special cutting machine that can cut iron plate with the type of material SUS409L measuring 341 x 328.5 x 1, and the machine must be able to synchronize with the running press work. Product development is carried out using the Design for Manufacturing and Assembly (DFMA) concept. The DFMA concept is related to the number of components, and assembly time. This research is expected to produce a cutting machine design that is in accordance with its function and considers aspects of manufacturing and assembly ease. The results of the design of the new cutting machine (HC21) product, the design efficiency value is 6.99% with a total of 23 components. While the Old Cutting Machine design (K56A) is 6.08% with 32 components. The results of this new design can reduce 9 components and increase assembly efficiency by 0.91%.